The child’s voice in migration literature: on Miguel Gane’s Când o să te faci mare / Cuando seas mayor - Bîscal (Oprea), Maria (Swedish Journal of Romanian Studies, 2026)
This article examines Când o să te faci mare / Cuando seas mayor [When you grow up] the debut novel of Spanish-language writer Miguel Gane, through the lens of child-centered migration narratives. The text offers an autobiographical portrayal of a Romanian boy’s emigration to Spain and the emotional, linguistic, and cultural tensions that shape his formative years. Structured as a sequence of episodic fragments, the novel foregrounds the child’s voice - fragile yet lucid - as a narrative instrument that renders the affective dimensions of uprooting, socioeconomic precarity, and identity reconstruction. Gane’s use of lyrical language, confessional tone, and symbolic anonymity (the nameless village, child, and parents) emphasizes migration as both a social condition and an inner process of loss and adaptation. Positioned within contemporary literature of the Romanian diaspora, the novel reveals the child’s oscillation between vulnerability and resilience, highlighting how memory, familial bonds, and the search for belonging constitute the core of the migrant experience. Through this perspective, the study underscores the originality of Gane’s contribution to migration literature and the significance of childhood as a site of both trauma and transformation.